The effects of mothers’ musical background on sedentary behavior, physical activity, and exercise adherence in their 5-6-years-old children using movement-to-music video program - Tuominen, Pipsa P. A. (PLoS One, 2018)
OBJECTIVES: The purpose of this study was to examine whether mothers’ musical background has an effect on their own and their children’s sedentary behavior (SB) and physical activity (PA). The aim was also to assess children’s and their mothers’ exercise adherence when using movement-to-music video program. DESIGN: Sub-group analysis of an intervention group in a randomized controlled trial (ISRCTN33885819). METHOD: Seventy-one mother-child-pairs were divided into two categories based on mothers’ musical background. Each pair performed 8 weeks exercise intervention using movement-to-music video program. SB and PA were assessed objectively by accelerometer, and exercise activity, fidelity, and enjoyment were assessed via exercise diaries and questionnaires. Logistic regression model was used to analyze associations in the main outcomes between the groups. RESULTS: Those children whose mothers had musical background (MB) had greater probability to increase their light PA during the intervention, but not moderate-to-vigorous PA compared to those children whose mothers did not have musical background (NMB). SB increased in both groups. Mothers in the NMB group had greater probability to increase their light and moderate-to-vigorous PA and decrease their SB than mothers in the MB group. However, exercise adherence decreased considerably in all groups. Completeness, fidelity, and enjoyment were higher among the NMB group compared to the MB group. CONCLUSIONS: The present results showed that mothers without musical background were more interested in movement-to-music exercises, as well as their children. For further studies it would be important to evaluate an effect of children’s own music-based activities on their SB and PA.